Som̐varaṇīra bāṭe bāṭa - Baruvā, Praphulla Gobinda (Sāhitya Prakāśa, 2023)
Autobiographical memoirs of an Assamese author
Keywords: Baruwā; Praphulla Gobinda; 1932-; Authors; Assamese; 20th century; Biography.